2016
DOI: 10.1186/s12891-016-0948-4
|View full text |Cite
|
Sign up to set email alerts
|

A double blind randomized active-controlled clinical trial on the intra-articular use of Md-Knee versus sodium hyaluronate in patients with knee osteoarthritis (“Joint”)

Abstract: BackgroundTo evaluate the clinical outcomes of a group of patients affected by knee osteoarthritis (OA) treated with MD-Knee (Guna S.p.a., Milan, Italy) versus a group of patients treated with sodium hyaluronate.MethodThis non-inferiority prospective randomized controlled trial involved 60 patients affected by knee OA, grade 2–3 of Kellgren-Lawrence scale. The MD-Knee Group, Group A (n = 29) was administered five intra-articular injections at 1 week interval; the sodium hyaluronate Group, Group B (n = 31), was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 18 publications
(12 reference statements)
2
28
1
1
Order By: Relevance
“…A limit of this study is represented by the lacking of studies aimed at characterizing the permanence and rheological and visco-elastic properties of MD-Tissue, however clinical studies are available demonstrating that the collagen-based medical compound is effective in osteoarticular pathologies [18,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A limit of this study is represented by the lacking of studies aimed at characterizing the permanence and rheological and visco-elastic properties of MD-Tissue, however clinical studies are available demonstrating that the collagen-based medical compound is effective in osteoarticular pathologies [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…No side effects, allergic reactions, nor drug interactions have been observed. Clinical data reported that treatment with MD-Knee, a collagen-based medical compound similar to MD-Tissue, for up to 6 months was generally well tolerated, and no systemic adverse events or septic complications were observed [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The first, by Furuzawa-Carballeda et al [20,21], showed a statistically significant improvement on VAS, WOMAC, and Lequesne indexes after 12 bi-weekly intra-articular injections of 2 mL (13.8 mg) pepsin-treated porcine polymerized, type I collagen versus as many placebo injections. More recently, a double-blind randomized controlled clinical trial on 29 patients [22] showed no significant differences in VAS and Lequesne scores at 3 or 6 months after treatment, in patients that were administered five intra-articular injections of 4 mL (concentration unknown) 300 kDa type I hydrolyzed porcine collagen at 1-week intervals versus patients that were given as many injections of 2.5 mL (25 mg) sodium hyaluronate. Recently, a novel injectable collagen formulation (ChondroGrid (CG), Bioteck, Arcugnano, Italy) consisting of bovine hydrolyzed <3 kDa type I collagen (4 mg/2 mL) has been developed and is currently available on the market as an injectable medical device.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, its degradation in the constituent amino acids constitutes a nutritional support for tissues of the other joint structures. MD-Knee preparation is equally effective in knee OA symptoms over six months after a five-week injection course as the HA formulation (SUPARTZ ® ) [32]. Moreover, 3 mL IAI of porcine type I atelocollagen (BioCollagen group) has been also demonstrated to alleviate knee pain in OA patients at 24 weeks [33].…”
Section: Discussionmentioning
confidence: 99%